2013
DOI: 10.1007/s00436-013-3675-x
|View full text |Cite
|
Sign up to set email alerts
|

Description of Leucocytozoon quynzae sp. nov. (Haemosporida, Leucocytozoidae) from hummingbirds, with remarks on distribution and possible vectors of leucocytozoids in South America

Abstract: We describe Leucocytozoon quynzae sp. nov. (Haemosporida, Leucocytozoidae), which is the first Leucocytozoon parasite identified to species level in hummingbirds. It was found in the Amethyst-throated Sunangel (Heliangelus amethysticollis, Trochilidae, Apodiformes) captured in the Palacio Forest, which belongs to the damping zone of Chingaza National Natural Park, Cundinamarca, Colombia, at 2,900 m above sea level where the transmission occurs; the new species were found both in the high Andean forest and Para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 40 publications
2
21
0
3
Order By: Relevance
“…The Neotropical region offers a great opportunity for research on avian haemoparasites; this study found new host-parasite relationships, most likely due to high avian diversity associated with the uplift of the Andes, and the scarce number of studies on this topic in the Andean region [7][8][9][10][11][12][13][14][15]40,54,55]. An increasing number of lineages from avian Haemosporida have been recorded in the last decade around the world.…”
Section: Discussionmentioning
confidence: 99%
“…The Neotropical region offers a great opportunity for research on avian haemoparasites; this study found new host-parasite relationships, most likely due to high avian diversity associated with the uplift of the Andes, and the scarce number of studies on this topic in the Andean region [7][8][9][10][11][12][13][14][15]40,54,55]. An increasing number of lineages from avian Haemosporida have been recorded in the last decade around the world.…”
Section: Discussionmentioning
confidence: 99%
“…That calls for the development of a new set of primer for nested PCR-based methods diagnosis of avian leucocytozoids. The new mtDNA genomes sequences obtained in this and previous studies conducted in the Neotropics (i.e., Matta et al, 2014; Lotta et al, 2016; Pacheco et al, 2018b) and now available in public databases can be helpful for the design of a new set of primer and PCR protocols.…”
Section: Discussionmentioning
confidence: 91%
“…Such host species richness seems to drive a high diversity of avian haemosporidian parasites that is just starting to be characterized using microscopy and Polymerase Chain Reaction (PCR)-based detection methods (i.e. Merino et al, 2008; Rodríguez et al, 2009; Jones et al, 2013; Mantilla et al, 2013, 2016; Matta et al, 2014; Galen and Witt, 2014; Harrigan et al, 2014; González et al, 2014, 2015; Marzal et al, 2015; Lotta et al, 2016; Moens et al, 2016; Moens and Pérez-Tris, 2016; Cadena-Ortiz et al, 2018; de Aguilar et al, 2018; Gil-Vargas and Sedano-Cruz, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Hypotheses to explain the low parasite prevalence in Neotropical countries compared to temperate regions include: (1) the great avian biodiversity present in the Neotropical region may lead to a dilution effect [81], decreasing the density of susceptible hosts. Such an effect would provide less opportunity for transmission [82]; (2) the life-history strategies of tropical birds, which are typically longer-lived than species at high latitudes, might include stronger immune defences against infection [14].…”
Section: Discussionmentioning
confidence: 99%